Reframing the semantic and pragmatic aspects of pun words in the Holy Quran from Arabic into English - AlAqad, Mohammed H.; Hawamdeh, Mohammad Amin; Kadhim, Kais (Research Journal in Advanced Humanities, 2023)
As the central point of Islam, the Quran is the link that connects humanity (the creation) with Allah (the creator). The translation of the Holy Quran is still a problematic issue in the Islamic theology due to its numerous Islamic terms that hold multiple or double meanings. Many of these problems are caused by the contradictory translations of puns (Tawriyah) and the misinterpretations between the intended meanings and their inherent notions, resulting in a certain amount of ambiguity. Translators and interpreters of the Quran face difficulties that make their task impossible to cater for this fact; consequently, they end up translating the superficial sense, which leads to a tremendous loss of either semantic or rhetoric features. Therefore, this research deals with the challenges of translating the meanings of puns (Tawriyah) as stated in the Quranic text into English. It examines eight selected verses from the Quran along with two widespread English translations by Shakir (2011) and Yusuf Ali (2014/1934). The research employs Delabastita᾿s (1996) typology of horizontal puns and Nida’s (1964) translation equivalence to identify the types of puns produced by the two translators and also determine the governed factors for mistranslating the meanings of puns in the Holy Quran from Arabic into English.